The Impact of Financial Development on Ecological Footprints of Nations - Ashraf, Ayesha (Archīum Ateneo, 2022)
Financial development is an important driver of technological progress in economic development. Its role in environmental change has not been well examined. We endeavor to examine the non-linear effects of multi-dimensional financial development measures on four kinds of ecological footprints in a global sample of 124 economies. We apply a two-step system generalized method of moments to deal with possible endogeneity. We find a stark difference in the impact of financial institutions' development and financial markets' development on the ecological footprints. Whereas financial institutions, with their three dimensions (i.e., depth, access, and efficiency) have an inverted-U shaped relationship with the ecological footprints, allowing for the initially harmful effect on the environment to revert to beneficial effects, the same results are not observed for financial markets. We attribute the inverse-U shaped relationship to a declining scale effect of FD and rising technological and composition effects of FD that transform the economy. Based on that we recommend that best practices of financial institutions regarding making environmentally conscious investment decisions be turned into a conscious investing culture around the world. For this to become a reality, better information-sharing regarding the individual environmental performance of firms will be needed.